PENGARUH DANA ALOKASI UMUM TERHADAP PERTUMBUHAN EKONOMI DENGAN BELANJA MODAL SEBAGAI VARIABEL MEDIASI (STUDI EMPIRIS PADA KABUPATEN/KOTA DI JAWA TENGAH) - Sundoro, Fredericho Mego; Suhardjo, Yohanes (Fakultas Ekonomi, Universitas Semarang, 2021)
ABSTRACT This study aims to determine the effect of DAU on Economic Growth with Capital Expenditure as a mediating variable related to the effect of DAU on Economic Growth. The research population is the Regency/City in Central Java. The research data were collected using the documentation method available at the Central Statistics Agency. The Sampling Technique uses the Saturated Sampling Technique, which means that the entire population is taken as a sample, as many as 35 districts/cities. Data analysis uses path analysis which includes the 1st path regression equation and 2nd path regression equation. Hypothesis testing using t test. The results of hypothesis testing show that: 1) DAU has an effect on Capital Expenditures; 2) DAU has no effect on Economic Growth; and 3) Capital Expenditure has no effect on Economic Growth; and 4) Capital Expenditure is not a mediating variable related to the effect of DAU on Economic Growth. Keywords: DAU, Capital Expenditure, Economic Growth, Mediation Variables, Path Analysis